Prospective evaluation of E6/E7 mRNA detection by the NucliSENS Easy Q HPV assay in a stepwise protocol. Issue 7 (22nd May 2013) - Padalko, Elizaveta; Van Renterghem, Lieve; Bamelis, Mieke; De Mey, Anja; Sturtewagen, Yolande; Vastenavond, Hilde; Weyers, Steven; Praet, Marleen
Abstract The objective of the study was to evaluate prospectively the added value of E6/E7 mRNA detection in a stepwise protocol. A total of 1, 422 samples were collected over a period of 17 months. The samples were referred for human papillomavirus (HPV) genotyping if they showed cytological evidence of atypical squamous cells of undetermined significance, low‐ or high‐grade squamous intraepithelial lesion. If one or more of HPV types 16, 18, 31, 33, or 45 were present, mRNA was analyzed by the NucliSENS EasyQ HPV assay. The genotypical distribution of high‐risk HPV was very heterogeneous; HPV 16, 18, 31, 33, and 45 represented 20.2%, 3.4%, 10.8%, 3.4%, and 3.8% of HPV‐positive samples, respectively. Follow‐up data were available for 35 patients. Although over the half (51.4%) of follow‐up samples showing HPV DNA/mRNA consensus evolved to cervical intraepithelial neoplastic lesions, 25.7% showed no progression to neoplasia despite mRNA positivity. However, the major concern was the group (14.3%) that showed progression to cervical intraepithelial neoplasia despite mRNA negativity: all but one of these cases had a high‐risk HPV genotype other than the five included in the NucliSENS EasyQ HPV assay. Markedly, 66.7% of the discordant samples between colposcopy and histology that underestimated the degree of cervical dysplasia were found in this group. Close monitoring of high‐risk HPV DNA‐positive/mRNA‐negative cases remains necessary, which leads to questions about the added value of the evaluated protocol. J. Med. Virol. 85:1242–1249, 2013. © 2013 Wiley Periodicals, Inc.